Al-Faruqi's Islamization of Science in Sardar's Critical Perspective - Istanto, Dwi; Zarkasyi, Hamid Fahmy; Arroisi, Jarman; Rachim, Dimas Kukuh Nur; Rusli, Ris'an (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2025)
This research conducts an in-depth analysis of Ziauddin Sardar's views on the concept of Islamization of science promoted by Ismail Raji al-Faruqi. By exploring the works of the two figures, this research reveals in detail Sardar's criticisms of the epistemological, paradigmatic and methodological foundations underlying the Islamization of science. The analysis shows that Sardar has fundamental concerns about the potential of the Islamization of science to limit the diversity of knowledge, shift established scientific paradigms, and sacrifice the rigor of research methodology. According to Sardar, attempts to impose Islamic views into all aspects of science risk stifling the development of science as a whole. This study also presents a more thoughtful interpretation. The author argues that the Islamization of science should not be understood as a way to completely overhaul established scientific paradigms and methods. Instead, the Islamization of science can be an opportunity to expand our understanding of natural phenomena by integrating Islamic perspectives. With descriptive analysis, this study concludes that the Islamization of science can be a bridge to a more comprehensive synthesis of knowledge, provided it is done wisely and avoids oversimplification. In responding to the concept of Islamization of science, Sardar offers constructive criticism. He reminds us to maintain harmony between religious values and academic autonomy in advancing science. While critical of certain aspects, Sardar does not entirely dismiss the concept. He advocates for a more inclusive and open dialogue among Muslim scientists and Islamic scholars to collaboratively develop a model of Islamization that is both relevant to contemporary challenges and compatible with the principles of scientific inquiry.